Nanoengineered Advanced Materials for Enabling Hydrogen Economy: Functionalized Graphene–Incorporated Cupric Oxide Catalyst for Efficient Solar Hydrogen Production (Global Challenges 3/2020). Issue 3 (2nd March 2020) - Dalapati, Goutam Kumar; Masudy‐Panah, Saeid; Moakhar, Roozbeh Siavash; Chakrabortty, Sabyasachi; Ghosh, Siddhartha; Kushwaha, Ajay; Katal, Reza; Chua, Chin Sheng; Xiao, Gong; Tripathy, Sudhiranjan; Ramakrishna, Seeram
Abstract : In article number 1900087, Goutam Kumar Dalapati and co‐workers develop a low cost, stable and efficient photocathode for sun‐light driven hydrogen generation. Copper oxide (CuO) functionalized with graphene enhances hydrogen generation through water splitting in presence of solar radiation. Hydrogen generation in this way is an effective path to address global challenges and can be used to minimize global warming by promoting hydrogen based green economy.